[tex]\displaystyle\lim_{x\to4}\frac{x^3-2x^2-9x+4}{x^2-2x-8}[/tex]
First notice that [tex]x^2-2x-8=(x-4)(x+2)[/tex]. If [tex]x-4[/tex] is not a factor of the numerator, then there is a non-removable discontinuity at [tex]x=4[/tex], and a removable discontinuity otherwise.
You have [tex]4^3-2\times4^2-9\times4+4=0[/tex], which means, by the polynomial remainder theorem, that [tex]x-4[/tex] is indeed a linear factor of the numerator. Dividing yields a quotient of
[tex]\dfrac{x^3-2x^2-9x+4}{x-4}=x^2+2x-1[/tex]
so the limit is
[tex]\displaystyle\lim_{x\to4}\frac{x^2+2x-1}{x+2}=\frac{4^2+2\times4-1}{4+2}=\frac{23}6[/tex]